Recruitment of older adults to three preventative lifestyle improvement studies - Chatters, Robin; Newbold, Louise; Sprange, Kirsty; Hind, Daniel; Mountain, Gail; Shortland, Katy; Powell, Lauren; Gossage-Worrall, Rebecca; Chater, Tim; Keetharuth, Anju; Lee, Ellen; Woods, Bob (BioMed Central, 2018)
Background: Recruiting isolated older adults to clinical trials is complex, time-consuming and difficult. Previous studies have suggested querying existing databases to identify appropriate potential participants. We aim to compare recruitment techniques (general practitioner (GP) mail-outs, community engagement and clinician referrals) used in three randomised controlled trial (RCT) studies assessing the feasibility or effectiveness of two preventative interventions in isolated older adults (the Lifestyle Matters and Putting Life In Years interventions). Methods: During the three studies (the Lifestyle Matters feasibility study, the Lifestyle Matters RCT, the Putting Life In Years RCT) data were collected about how participants were recruited. The number of letters sent by GP surgeries for each study was recorded. In the Lifestyle Matters RCT, we qualitatively interviewed participants and intervention facilitators at 6 months post randomisation to seek their thoughts on the recruitment process. Results: Referrals were planned to be the main source of recruitment in the Lifestyle Matters feasibility study, but due to a lack of engagement from district nurses, community engagement was the main source of recruitment. District nurse referrals and community engagement were also utilised in the Lifestyle Matters and Putting Life In Years RCTs; both mechanisms yielded few participants. GP mail-outs were the main source of recruitment in both the RCTs, but of those contacted, recruiting yield was low (< 3%). Facilitators of the Lifestyle Matters intervention questioned whether the most appropriate individuals had been recruited. Participants recommended that direct contact with health professionals would be the most beneficial way to recruit. Conclusions: Recruitment to the Lifestyle Matters RCT did not mirror recruitment to the feasibility study of the same intervention. Direct district nurse referrals were not effective at recruiting participants. The majority of participants were recruited via GP mail-outs, which may have led to isolated individuals not being recruited to the trials. Further research is required into alternative recruitment techniques, including respondent-driven sampling plus mechanisms which will promote health care professionals to recruit vulnerable populations to research. Trial registration: International Standard Randomised Controlled Trial Registry, ID: ISRCTN28645428 (Putting Life In Years RCT). Registered on 11 April 2012; International Standard Randomised Controlled Trial Registry, ID: ISRCTN67209155 (Lifestyle Matters RCT). Registered on 22 March 2012; ClinicalTrials.gov, ID: NCT03054311 (Lifestyle Matters feasibility study). Registered retrospectively on 19 January 2017.